Technique of A Feasibility Study for the Use of a Variable Frequency Drive in Pumping Units - Khafizov Islom Ikramovich; Hafizov Xudoyor Islomovich; Ahmadov Elmurod Kamol o'g'li (Genius Journals, 2022)
The article presents the methodology of a feasibility study for the use of variable frequency drives in pump units. The calculation methodology of the application of the variable frequency drive in pump units is presented and it is proved that its application makes it possible to use large pump units in low-flow mode and, therefore, to reduce their total number. The problem of determining the technical and economic parameters of D-series pumps is also considered and it is shown that the linear dimensions of pump units grow much slower than their capacity and flow rate. An expression for determining the relative linear dimensions of the units being compared is given
Keywords: Units, pump units, D-series